High-order stimulated Raman scattering in tetragonal CaYAlO4 crystal-host for Ln3+-lasant ions - Kaminskii, A. A. (2013)
Multiple Stokes and anti-Stokes χ(3)-nonlinear generation in the tetragonal crystal of CaYAlO4 was observed at 300 K and ≈ 9 K under picosecond excitation in the visible spectral range. All the recorded Raman induced laser lines were identified and attributed to the SRS-promoting vibration mode of octahedral [AlO6]-9 units of the crystal.